The "Re-Colonising" of Pitcairn - Farran, Sue (Victoria University of Wellington Law Review, 2007)
The criminal trials of Pitcairn islanders on charges of rape and sexual assault have attracted considerable media notoriety and some academic comment in New Zealand and elsewhere. However question marks remain; not as regards the guilt or otherwise of the accused but in respect of the means whereby they were brought to trial. In particular the legal reasoning used to exercise imperial rule over Pitcairn and the embroilment of New Zealand in the "Pitcairn case" deserves scrutiny. This article critically considers how the courts, including the Privy Council, determined that Pitcairn Islanders were British subjects and therefore within the exercise of Her Majesty’s prerogative powers and which law was applicable to them, and the consequences of that process, both for Pitcairn as well as New Zealand.